Análise da estrutura arbustivo-arbórea de uma área de cerrado sensu stricto, município de Aquidauana-Mato Grosso do Sul - Fina, Bruna Gardenal; Monteiro, Reinaldo [UNESP] (Sociedade de Investigações Florestais, 2013)
The objective of this work was to study the floristic composition and structure of the Cerrado (Brazilian savannah), focusing on the tree and shrub strata. A total of 30 plots (10x10m) were set up, distributed in 10 contiguous blocks where individuals with a minimum PBH of 10 cm were sampled. A total of 1,107 individuals were sampled. Such individuals belonged to 33 families and 88 species, showing high values of richness. Total basal area and total density were respectively 6,651m² and 3690 individuals per hectare. The values of diversity (3.868 nats/individual) and evenness (0.86) show high heterogeneity and low ecological dominance. The most important species were Qualea grandiflora Mart., Lafoensia pacari St. Hil., Magonia pubescens St. Hil. and Qualea parviflora Mart., which together represented 57.7% of VI.

Este trabalho teve como objetivo registrar a composição florística e estrutura de uma área de Cerrado stricto senso, com ênfase no estrato arbustivo-arbóreo. Foram instaladas 30 parcelas de 10 x 10 m, distribuídas em blocos de 10 parcelas contíguas, onde os indivíduos com PAP superior ou igual a 10 cm foram incluídos. O número total de indivíduos amostrados foi de 1.107, pertencentes a 33 famílias e 88 espécies, evidenciando-se alta riqueza. A área basal total e a densidade total foram, respectivamente, de 6,651 m² e 3.690 indivíduos por hectare. Os valores de diversidade (3.868 nats/indivíduo) e equabilidade (0,86) indicaram grande heterogeneidade e baixa dominância ecológica. As espécies mais importantes foram Qualea grandiflora Mart., Lafoensia pacari St. Hil., Magonia pubescens St. Hil e Qualea parviflora Mart., que juntas representaram 57,7% do VI
A woody community structure in a cerrado sensu stricto area, municipality of Aquidauana-Mato Grosso do Sul
Keywords: Cerrado; Fitossociologia; Mato Grosso do Sul; Cerrado; fitossocioly; Mato Grosso do Sul State, Brazil